ESTIMATIVA POPULACIONAL EM NINHOS DE ACROMYRMEX SUBTERRANEUS SUBTERRANEUS FOREL, 1893 (HYMENOPTERA: FORMICIDAE) - PEREIRA, ROZIMAR DE CAMPOS; Lucia, Terezinha Maria Castro Della (Revista Ceres, 2015)
-